(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The World Wide Web is now a practical medium for customers, informationseekers, business owners and entrepreneurs. The increase of the flexibility and power of wireless deals provides proper opportunities for rising upservices to customers. In today’s scenario of business mobile commerce or M-Commerce has entered infinance, services, retails, and telecommunication and information technologyservices. In these sectors, M-Commerceis not only being widely accepted but also it is being more used as a popular way of business. Inthis paper I try to provide anoverview of the fundamentals about m-commerce and e-commerce. This paper attempts to help businessmanagers, to understand the key elements and basic issues of m-commerce and to assess the impact ofm-commerce on current and future businesses. In this paper I view M-Commerceare going beyond E-commerce.M-Commerce is doing all work which was done by E-Commerce by using mobileterminals over a wirelessnetwork. Finally, I’ll look briefly into the situations of the mobile telephony market both in world andIndia.